PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN BUMN SEKTOR KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Pertiwi, Dea Putri; Fajar Rina Sejati; Ponto, Sahrul (Publika Citra Media, 2024)
This research aims to test and obtain empirical evidence regarding the influence of the Board of Directors, Board of Commissioners and Audit Committee on Financial Performance. This research uses a sample of state-owned construction sector companies listed on the Indonesia Stock Exchange in 2018-2022. The research method used in this research is the purposive sampling method using SPSS 21 for data analysis. This type of research is quantitative with a population of 22 companies and 9 companies used as research samples with 5 (five) years of observation, so the total research sample is 45 samples. The analysis technique used is multiple linear regression. The results of this research indicate that the Board of Directors and Audit Committee have no effect on Financial Performance. Meanwhile, the Board of Commissioners has a negative influence on Financial Performance.